Imaging findings of Budd-Chiari syndrome caused by intravenous leiomyomatosis: a case report - Wang, Yahong; Dong, Yifan; Tian, Xueyu; Chen, Yu; Yang, Xiao; Li, Jianchu (Frontiers in Medicine, 2024)
Intravenous leiomyomatosis (IVL) is a rare gynecological-related tumor. It can invade and extend in the blood vessel and eventually involve the cardiac cavity or even the pulmonary artery. IVL generally does not adhere to the vein wall and infrequently leads to the manifestation of Budd-Chiari syndrome (BCS).In this case report, the presence of a sizable tumor obstructed the second hepatic portal, impeding the return flow of the hepatic veins, thereby precipitating the development of BCS. The presence of collateral veins and dilation of the accesssory hepatic vein were identified through computed tomography venography and ultrasonography, thus supporting the diagnosis of BCS. The patient underwent a comprehensive surgical resection and was found to have a favorable prognosis.